THE DEFENSE OF HADITH SCHOLARS AGAINST AHL AL-RA’Y MADHHAB (Study of Thought Shaikh ‘Abd al-Fattâh Abû Ghuddah) - Adi Abdullah Muslim (Jurnal Ushuluddin, 2019)
Debate between hadith scholar and Islamic jurisprudence has occurred since the time of the founding of fiqh madhhab that was dominated by Imam Abû Hanîfah in Kufah (as a representation of ra’y), and Imam Malik in Medina (as a representation of hadith scholar). Then the figure of Imam al-Shafi’i emerged as the mediator for them, he was given the title Nasir al-Sunnah. This study explains the existence of scholars of hadith - Shaikh Abd al-Fattâh Abû Ghuddah - who adhered to Ahl al-Ra’y madhhab of Imam Abû Hanîfah, defended the accusations against his madhhab, and also wanted to prove that Imam Abû Hanîfah was a textualist. This is a library research using content analysis. This study indicated that Imam Abû Hanîfah who was held by Abû Ghuddah as Ahl-al-ra’y madhhab did not make his madhhab understanding be rationalist in the field of hadith. He often in issuing fatwas based on ra’y. As a textualist cleric, he put nash in perseverance not prioritize qiyas and reason